The Factors That Affect Diet Compliance in Patients with Diabetes Mellitus at Nganjuk Hospital - sony wahyu tri cahyono (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Abstract Patients with diabetes mellitus must follow a strict diet to control blood sugar levels to keep them within normal limits. If it is not controlled, it will cause various diseases which will be caused by visual disturbances, cataracts, heart problems, impaired kidney function, sexual impotence, difficulty in healing wounds or even rot/gangrene, lung infections, vascular disorders, and strokes. The purpose of this study was to determine the factors that affect dietary compliance in diabetes mellitus sufferers. This study uses a qualitative method with a phenomenological approach. This study explores the experiences of people with diabetes mellitus when they are on a diet. The participants in this study were 10 people. The technique of collecting data was by conducting in-depth interviews so that the results were 3 themes, namely lack of knowledge about diet, lack of family support, and difficulty in adhering to a diet. The importance of support and motivation from family and health workers for diabetes mellitus sufferers to always adhere to a diet to avoid various complications. Keywords : Diabetes Mellitus, and Diet Compliance